Consumption of a literary tourism place: a perspective of embodiment. Issue 1 (1st January 2020) - Jiang, Liao; Yu, Larry
Abstract: With contemporary cultural transformation and the expansion of consumption, tourism has been elevated to embodied consumption of the entire tourist destination. This study examined the case of Liangshan in the Shandong province – the birthplace of the famous story of Water Margin in Chinese classical literature – to construct an analytical framework for the consumption of literary tourism. Using data collected from personal interviews and online blogs and analyzed by content analysis, this study determined the relational structure of literary tourist embodied consumption. Research findings revealed that the existence of literary works as a 'preconstruction' or 'preunderstanding' was an expectation of literary tourists. There were different dimensions of embodied consumption of literary tourism, which were interdependent and mutually permeating. Perception, imagination, understanding, and emotion are mutually evocative in the multisensory experience of a literary tourism place. This study contributes to theory by providing further understanding of literary tourists' aesthetic experience of embodied consumption and offers implications for literary tourism resource development, local destination brand marketing, and the inheritance of humanistic values.